Responses - Kamm, Frances (Journal of moral philosophy, 2014)
In this essay I respond to commentators on Ethics for Enemies, including (1) Caspar Hare on torture and other harms imposed on an agent after his act, (2) Suzanne Uniacke on conceptual issues related to terrorism, (3) Thomas Hurka on right reason and proportionality conditions in the justice of going to war (jus ad bellum), (4) Jeff McMahan on liability, proportionality, and harm in jus ad bellum, and (5) Gabriella Blum and John Goldberg on the moral and legal status of action prompted by bad intentions.